2015
DOI: 10.1002/ccr3.260
|View full text |Cite
|
Sign up to set email alerts
|

2q31.1 microdeletion syndrome: case report and literature review

Abstract: Key Clinical MessageWe describe a preterm neonate with bilateral coloboma of the iris, upper and lower limb malformations including rocker bottom feet, camptodactyly, and clinodactyly together with microcephaly and small for gestational age whom cytogenetic diagnosis using SNP microarray detected an interstitial deletion of chromosome 2 between 2q31.1 and 33.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Furthermore, given that the use of CGH has allowed a better characterization and de nition of the breakpoints of deletions in the DNA, different syndromes are now recognized affecting these regions: the 2q31.1 microdeletion syndrome, 2q31.2q32.3 microdeletion syndrome, and the 2q33.1 microdeletion syndrome. [10] However, our patient had deleted region from all 2q31 cytobands and a large part of the 2q32.1 cytoband, making more complex her phenotype and the determination of what genes are contributing to it when compared to other cases.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, given that the use of CGH has allowed a better characterization and de nition of the breakpoints of deletions in the DNA, different syndromes are now recognized affecting these regions: the 2q31.1 microdeletion syndrome, 2q31.2q32.3 microdeletion syndrome, and the 2q33.1 microdeletion syndrome. [10] However, our patient had deleted region from all 2q31 cytobands and a large part of the 2q32.1 cytoband, making more complex her phenotype and the determination of what genes are contributing to it when compared to other cases.…”
Section: Discussionmentioning
confidence: 77%
“…Severe limb deformities, including split hand and monodactyly, have also been reported, and DLX1 and DLX2 are speculated to be novel candidate genes. 5 , 14 , 28 However, upper and lower limb malformations in the examined fetus did not confirm this possibility. Theisen et al 29 have reported individuals exhibiting deleted DLX1/DLX2 integrally, and no obvious limb phenotype was detected.…”
Section: Discussionmentioning
confidence: 86%
“…Severe limb deformities, including split hand and monodactyly, have also been reported, and DLX1 and DLX2 are speculated to be novel candidate genes 5,14,28 . However, upper and lower limb malformations in the examined fetus did not confirm this possibility.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations